Human papillomavirus: etiology, pathogenesis, role, and importance in the development of cervical cancer: A review - Aydar M. Ziganshin; Sergej V. Keidar; Regina Sh. Khalitova; Airat R. Mulyukov; Emiliya N. Muhamed'yarova (IP Berlin A.V., 2023)
Human papillomavirus (HPV) is now considered the most common sexually transmitted infection. Since the discovery by Nobel laureate Harald zur Hausen (2008) of HPV as a virus with a high carcinogenic risk, the strategy for screening and prevention of this disease has changed dramatically. It has significantly increased the relevance of the study of this infection. Although HPV is not life-threatening, its highly oncogenic subtypes can lead to the development of cervical cancer with high mortality.